Effects of High-Intensity Interval Training With Specific Techniques on Jumping Ability and Change of Direction Speed in Karate Athletes: An Inter-individual Analysis - Ojeda-Aravena, Alex; Herrera-Valenzuela, Tomás; Valdés-Badilla, Pablo; Martín, Eduardo Báez-San; Cancino-López, Jorge; Gallardo, Jairo Azócar; Zapata-Bastías, José; García-García, José Manuel (Frontiers in Physiology, 2021)
This study investigated the effect of 4weeks of high-intensity interval training (HIIT) with specific techniques and analyzed inter-individual variability [classified in responders (Rs) and non-responders (NRs)] on jumping ability and change of direction speed (CODS) in youth karate athletes. Athletes of both genders (n=10) were randomly assigned into experimental group (EG; n=5) and the control group (CG; n=5). The EG trained 2–3days per week applying HIIT (three rounds [15 sets of 4s all-out specific efforts with 8s of dynamical pauses] with 3min of recovery between rounds) during their usual training during 4weeks. Assessments included squat jump (SJ) and countermovement jump (CMJ) and CODS by T-test. No significant interaction effect group by time was found. Although, in percentage and effect size (ES) terms increases were reported in both groups for SJ (EG: 15.2%, ES=0.91 vs. CG: 12.4%, ES=0.02) and only in EG for the T-test (−1.7%; ES=−0.35). In turn, a trend toward a higher proportion of Rs was observed in the EG (40% Rs) vs. CG (20% Rs) for SJ and CODS, respectively. In conclusion, the addition to regular training of a HIIT with specific techniques and based on the temporal combat structure after 4weeks was not a sufficient stimulus to increase jumping ability and CODS in karate athletes.